Efektivitas Penggunaan Media Permainan Ludo Kimia Berbasis Chemo-Edutainment (CET) Pada Materi Sistem Koloid Terhadap Hasil Belajar Siswa Kelas XI SMAN 3 Pariaman - Lola Indriliza; Iswendi Iswendi (Universitas Negeri Padang, 2019)
This research is motivated by the lack of student participation in doing the exercises and the ineffectiveness of individual training because they are not competitive. This study aims to reveal the effectiveness of the use of chemo-edutainment-based ludo chemical (CET) games on the Colloid System material on the learning outcomes of class XI students of SMAN 3 Pariaman. The type of research used was a quasi-experimental design with a non-equivalent control group design. The population in this study were students of class XI MIPA SMAN 3 Pariaman. The research sample was taken using a purposive sampling technique so that the XI MIPA 1 class was selected as the experimental class and XI MIPA 2 class as the control class. Research data includes learning outcomes from the cognitive domain. The research instrument is a test of learning outcomes in the form of multiple choice questions that have been tested. The data analysis technique used was the two average similarity test (t-test) to determine the differences in learning outcomes and the N-Gain test to determine the increase in student understanding. The results showed an increase in understanding of learning outcomes that were better in the experimental class than in the control class. This is evidenced by the average posttest value of the experimental and control classes of 84.33 and 78.78 respectively and supported by hypothesis testing carried out by the t-test, namely count (2.607) bigger than t1-alpha (1.67) at the level of reality alpha = 0.05 with dk = 70 and opportunities t0.95. This is also evidenced by the average experimental class N-Gain test of 0.77 with a high category and a control class of 0.67 with a moderate category. Thus it can be concluded that the use of media is an effective game of ludo chemical chemo-edutainment (CET) with a high category in improving the learning outcomes of class XI students of SMAN 3 Pariaman.